2013
DOI: 10.1186/1475-9276-12-25
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status on changes in the general and mental health of women over time: evidence from a longitudinal study of Australian women

Abstract: IntroductionGenerally, men and women of higher socioeconomic status (SES) have better health. Little is known about how socioeconomic factors are associated with changes in health as women progress through mid-life. This study uses data from six survey waves (1996 to 2010) of the Australian Longitudinal Study on Women’s Health (ALSWH) to examine associations between SES and changes in the general health and mental health of a cohort of women progressing in years from 45–50 to 59–64.MethodsParticipants were 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
2
20
0
3
Order By: Relevance
“…32 Furthermore, it is responsive to change over time. [33][34][35] The Mental Health Index contains five items measuring: nervousness; low mood; feeling down; feeling calm and peaceful; and being happy. Scores range from 0 to 100, with higher scores indicating better mental health.…”
Section: Methodsmentioning
confidence: 99%
“…32 Furthermore, it is responsive to change over time. [33][34][35] The Mental Health Index contains five items measuring: nervousness; low mood; feeling down; feeling calm and peaceful; and being happy. Scores range from 0 to 100, with higher scores indicating better mental health.…”
Section: Methodsmentioning
confidence: 99%
“…Socioeconomic factors (particularly parental education) are also implicated in externalizing problems in adolescents (Amone-P' Olak et al, 2009;Bøe et al, 2012;Huisman et al, 2010), including aggression (Amone-P'Olak et al, 2009), delinquency or misconduct (Amone-P' Olak et al, 2009;Bøe et al, 2012), and symptoms of attention-deficit/hyperactivity disorder (Amone-P' Olak et al, 2009;Bøe et al, 2012; National Center for Health Statistics, 2012). There is also evidence that lower SES impedes the gradual increase in mental health that occurs during mid-to later adulthood (Williams, Cunich, & Byles, 2013).…”
Section: Socioeconomic Status and Mental Healthmentioning
confidence: 99%
“…In a natural experiment of the SES-health gradient, one study showed that individuals coming from U.S. states that had compulsory school laws show better self-rated health, less cardiovascular disease, fewer weight problems, and lower mortality rates (Fletcher, 2015;Lleras-Muney, 2005). Lower SES also hastens the gradual decline in health that begins in middle adulthood (Williams, Cunich, & Byles, 2013).…”
Section: Socioeconomic Status and Physical Healthmentioning
confidence: 99%
See 2 more Smart Citations